Past and possible future influence of the Atlantic Meridional Overturning Circulation on the climate responsible for concentration of geopolitical power and wealth in the North Atlantic region. (October 2019) - Railsback, L Bruce
Previous research has shown that nations that controlled global-scale empires over the most recent centuries and presently possess great per-capita wealth are in Earth's two largest regions of regular moderate rainfall. That rainfall regime is the pattern of atmospheric precipitation most supportive of agriculture and water-wheel-powered industry, both of which presumably contributed to those nations' advancement. Those regions of regular moderate rainfall ring the North Atlantic, and this article reviews the evidence that the Gulf Stream delivers warm vapor-releasing water in the upper limb of the Atlantic Meridional Overturning Circulation, generating the distinctive climate of western Europe and eastern North America. Ocean circulation's control on continental climate has thus contributed significantly to the Euro-American concentration of wealth and geopolitical power that has dominated the last few centuries of human history. However, comparison of the present apparent weakening or failure of the Atlantic Meridional Overturning Circulation with both the early Holocene 8.2 ka event and modeling of the Atlantic Meridional Overturning Circulation's diminished generation of water vapor suggests that Europe and eastern North America may lose their beneficent climate pattern as rainfall there lessens.